Analisis Pengaruh Motivasi terhadap Loyalitas Karyawan yang Dimediasi oleh Kepuasan Kerja pada The Mansion Resort Hotel dan Spa Ubud - Erika Vetriani, Ni Luh; Ayu Wimba, I Gusti; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Tight competition in the hotel industry encourages every business actor to increase employee loyalty in order to compete and develop. The problem of employee loyalty is also faced by The Mansion Resort Hotel dan Spa Ubud, Bali and based on the results of the pre-survey, it was found that there were problems related to motivation and job satisfaction. The aim of this research is to determine the role of job satisfaction in mediating motivation on employee loyalty. This research was conducted by The Mansion Resort Hotel dan Spa Ubud, Bali involving all 98 employees using the saturated sample or census method. Primary data collection was carried out using a questionnaire. The results of the respondents' answers were continued with validity and reliability tests, then continued with hypothesis testing using path analysis and Sobel test. The results of the analysis show that 1) motivation has a positive and significant effect on job satisfaction, 2) motivation has a positive and significant effect on employee loyalty, 3) job satisfaction has a positive and significant effect on employee loyalty, 4) job satisfaction has a positive and significant effect in mediating motivation on employee loyalty.